Feminized cultural capital at work in the moral economy: Home credit and working‐class women. Issue 1 (11th August 2022) - Marks, Abigail; Terry, Esme; Canduela, Jesus; Dakessian, Arek; Christopoulos, Dimitris
Abstract: One of the defining features of the home credit sector is the role played by its agents—workers who act as intermediaries between lending companies and borrowers to facilitate lending and collect repayments. There is a prevailing and pervasive narrative in the sector that women make superior agents, largely based on the belief that female agents can manage relationships with borrowers more successfully than their male counterparts. This article analyzes data from 349, 078 home credit accounts (loans), as well as 71 interviews with home credit agents and lending company managers, to evaluate both the myths and realities of women's roles in home credit. The data is also used to explore the opportunities for—and potential constraints on—women's career progression in home credit work, based on an understanding of the moral economy in which they operate. By exploring the moral economy of low‐income communities, the article highlights the role of working‐class women's cultural capital within the labor market. Despite women forming the majority of the agent workforce in home credit, women's capital is undervalued in comparison with their male counterparts' capital. The analysis within this article allows a greater understanding of the highly classed and gendered nature of the moral economy of low‐income communities and the exchange value of women's capital within the labor market.